2014
DOI: 10.5296/jebi.v1i1.6657
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Customer Loyalty, Perceived Service Quality and Customer Satisfaction: Brief on Saudi Grocery Stores

Abstract: Lack perceived quality in Saudi Arabia has been repeatedly identified as one of the most formidable barriers to people for engaging in customer loyalty.Despite, the widespread establishment of shopping malls all over the country, the statistics revealed that Saudi consumers, although trying grocery shopping in some shopping malls, still prefer to do their grocery shopping activities in traditional grocery stores and convenience stores (Othaim, 2012).This paper provides an overview perceived service quality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 219 publications
(54 reference statements)
2
11
0
Order By: Relevance
“…Results indicate that service quality is strongly associated with trust and satisfaction while weakly associated with customer commitment. This is consistent with various previous studies such as Yan et al (2011); Beneke et al (2012); Al Otaibi and Yasmeen (2014).…”
Section: Discussionsupporting
confidence: 94%
“…Results indicate that service quality is strongly associated with trust and satisfaction while weakly associated with customer commitment. This is consistent with various previous studies such as Yan et al (2011); Beneke et al (2012); Al Otaibi and Yasmeen (2014).…”
Section: Discussionsupporting
confidence: 94%
“…Yee et al (2011) revealed that service quality, customer satisfaction, and employee loyalty have a positive influence on customer loyalty, especially in the high-contract service industry. Moreover, Otaibi and Yasmeen (2014) attempted to study perceived service quality and customer satisfaction, which affect Saudi customer loyalty, and reviewed relevant previous studies that investigated the relationships among the said three variables.…”
Section: Customer Loyaltymentioning
confidence: 99%
“…In an increasingly competitive business environment in which marketers and customercentric organisations recognise the cost incurred in acquiring a new customer far exceeds that required to sustain the relationship with an existing customer (Myler, 2016); the Service quality in supermarket sector favourable effect of service quality (Ladhari, 2009) and customer satisfaction (Lam et al, 2004) on loyalty; and the positive relationship that exists between customer loyalty and profitability (Bowen and Chen, 2001), "the issue of customer loyalty is becoming increasingly important" (Baumann et al, 2012, p. 148). However, researchers (Al Otaibi and Yasmeen, 2014) suggest that considering the complexity of the effect of service quality and customer satisfaction on customer loyalty, further investigation is warranted. Kyle et al (2010) propose that the two recognised dimensions of loyalty are the attitudinal dimension (customers repurchase intention and willingness to recommend the service to others) and behavioural dimension (repeat purchases).…”
Section: Customer Loyaltymentioning
confidence: 99%
“…Fiji is one such developing nation whose supermarket sector is dwarfed by Australian and Pacific Rim countries and forms the basis of this study; it, nonetheless, is caught up in the tides of change and insatiable competition of the global supermarket sector. Against this backdrop, the growth of domestic supermarkets and entry of multinational supermarket chains into developing countries (Reardon and Gulati, 2008), in addition to increasing population, urbanisation and disposable income, have resulted in dramatic changes in supermarket customer's consumption patterns, service expectations, satisfaction and loyalty (Al Otaibi and Yasmeen, 2014) and have challenged and necessitated ever-changing, enhanced offerings by supermarkets. Hence, even in developing countries, a supermarket's service encounter process and delivery of superior service quality are not only critical to differentiate from competitors (Kitapci et al, 2013) and to improve customer satisfaction (Jamal and Anastasiadou, 2007), but also to build loyal customers critical for business survival and success (Kursunluoglu, 2014).…”
Section: Introductionmentioning
confidence: 99%